The germination of bush mint (Hyptis marrubioides EPL.) seeds as a function of harvest stage, light, temperature and duration of storage - doi: 10.4025/actasciagron.v33i4.4611 - Sales, Juliana de Fátima; Pinto, José Eduardo Brasil Pereira; Oliveira, João Almir de; Botrel, Priscila Pereira; Silva, Fabiano Guimarães; Corrêa, Ricardo Monteiro (Acta Scientiarum. Agronomy, 2011)
This study evaluated the effect of light, temperature, physiologic stage at harvest and length of time on the germination of Hyptis marrubioides seeds. Two trials were conducted. The first experiment was performed immediately after the seed harvest and consisted of a 2 x 3 x 3 factorial design with 2 environmental conditions (light and dark), 3 temperatures (20, 30 and 20/30ºC) and 3 seed harvest times (green colored seeds, light brown seeds and dark brown seeds). The second experiment was conducted in the presence of light at a temperature of 30ºC and consisted of a 4 x 3 factorial design, with 4 storage times (0, 6, 12 and 18 months) and the 3 three harvest physiologic stages used in the previous experiment. Both of the experiments were conducted in randomized blocks, with 4 replications of 100 seeds. Light did not affect germination. By contrast, a temperature of 20ºC retarded the germination process, although the percentage of germinating seeds was not affected. Seed storage and the different harvest physiologic stages affected the Speed of germination index (SGI) and the germination percentage. Seeds that were harvested at the more mature stage (dark brown color) could be stored for up to 18 months.